Security of Supply for Natural Gas Markets. What is it and What is it not? - Giacomo Luciani (Fondazione Eni Enrico Mattei (FEEM), 2004)
The issue of security of gas supplies is frequently discussed on the basis of intuitive and non-systematic arguments. Greater import dependence is normally equated with greater insecurity, and strategic stocks are the risk management tool most commonly considered. This paper strives to offer a systematic framework of analysis and shows that import dependence does not necessarily entail greater insecurity actually, the opposite may well be the case. It also discusses several alternatives to strategic stocks for risk management, which are more interesting and promising.
Keywords: Q41; Q43; 330; Natural gas market; Security of supply; Energieversorgung; Erdgasmarkt; Welt